Educational Design for MOOCs: Design Considerations for Technology-Supported Learning at Large Scale - Sergis, S.; Sampson, Demetrios; Pelliccione, Lina (Springer Nature, 2017)
© Springer-Verlag Berlin Heidelberg 2017. Massive open online courses (MOOCs) are a recent trend in the field of online learning. Their potential distinctive educational innovation is attributed mainly to their “Massiveness” and “Openness” dimensions. These two characteristics introduce new educational design considerations for accommodating the challenging demands of “Massiveness” and “Openness.” This is particularly pressing, since commonly recognized “shortcomings” of MOOCs, such as high participant drop-out rates and low levels of participant engagement and motivation, have been associated to the educational design of MOOCs. Within this context, this chapter discusses issues related with the educational design of MOOCs with emphasis to cultural and motivational issues, presents an analysis of existing educational design frameworks and/or guidelines for MOOCs and, finally, proposes an ADDIE-based educational design considerations framework (EDCF) for MOOCs, which incorporate the “Massiveness” and “Openness” requirements.